Ablation of GSDMD Improves Outcome of Ischemic Stroke Through Blocking Canonical and Non-canonical Inflammasomes Dependent Pyroptosis in Microglia - Wang, Kankai; Sun, Zhezhe; Ru, Junnan; Wang, Simin; Huang, Lijie; Ruan, Linhui; Lin, Xiao; Jin, Kunlin; Zhuge, Qichuan; Yang, Su (Frontiers in Neurology, 2020)
Ischemia/reperfusion (I/R) injury is a significant cause of mortality and long-term disability worldwide. Recent evidence has proved that pyroptosis, a novel cell death form, contributes to inflammation-induced neuron death and neurological function impairment following ischemic stroke. Gasdermin D (GSDMD) is a newly discovered key molecule of cell pyroptosis, but its biological function and precise role in ischemic stroke are still unclear. The present study investigates the cleavage activity of GSDMD, localization of pyroptotic cells and global neuroinflammation in gsdmd -/- mice after I/R. The level of cell pyroptosis around the infarcted area was significantly increased in the acute phase of cerebral I/R injury. Ablation of GSDMD reduced the infraction volume and improved neurological function against cerebral I/R injury. Furthermore, we confirmed I/R injury induced cell pyroptosis mainly in microglia. Knockdown of GSDMD effectively inhibited the secretion of mature IL-1β and IL-18 from microglia cells, but did not affect the expression of caspase-1/11 in vitro and in vivo. In summary, blocking GSDMD expression might serve as a potential therapeutic strategy for ischemic stroke.